2022
DOI: 10.1007/s00436-022-07445-3
|View full text |Cite
|
Sign up to set email alerts
|

The evolving story of Borrelia burgdorferi sensu lato transmission in Europe

Abstract: Beside mosquitoes, ticks are well-known vectors of different human pathogens. In the Northern Hemisphere, Lyme borreliosis (Eurasia, LB) or Lyme disease (North America, LD) is the most commonly occurring vector-borne infectious disease caused by bacteria of the genus Borrelia which are transmitted by hard ticks of the genus Ixodes. The reported incidence of LB in Europe is about 22.6 cases per 100,000 inhabitants annually with a broad range depending on the geographical area analyzed. However, the epidemiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 243 publications
(335 reference statements)
2
31
2
2
Order By: Relevance
“…We refer to pathogenic Borreliella species collectively as the LD spirochetes. LD spirochetes are maintained in nature in an enzootic cycle involving Ixodes species ticks and diverse vertebrate reservoirs ( 5 , 6 ). The CDC reported in 2016 that Ixodes scapularis and Ixodes pacificus ticks, the primary vectors for LD in North America, are present in 49.2% of United States counties ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…We refer to pathogenic Borreliella species collectively as the LD spirochetes. LD spirochetes are maintained in nature in an enzootic cycle involving Ixodes species ticks and diverse vertebrate reservoirs ( 5 , 6 ). The CDC reported in 2016 that Ixodes scapularis and Ixodes pacificus ticks, the primary vectors for LD in North America, are present in 49.2% of United States counties ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…12 Anthropogenic data characterizing human outdoor activity or human exposure to infected tick is challenging to collect. 8 Yet, recent citizen science research have shown promising results on characterizing human exposure to tick bite. 13 In addition, large-scale exploration of these above variables in relation to human LB occurrence in a comprehensive framework has not yet been done.…”
Section: Introductionmentioning
confidence: 99%
“…7 The presence and abundance of infected ticks therefore depend on the distribution of animal hosts, as well as suitable climates and vegetation habitats, allowing host-seeking, molting, and the completion of Ixodes’ life cycle (egg, larvae, nymph and adult). 8 Spillover to humans can occur through the bite of infected ticks, during outdoors activities. Understanding the spatial heterogeneity of LB incidence in humans therefore necessitate to account for environmental, meteorological factors and animal hosts’ distribution that can influence the presence and abundance of infected ticks, as well as humans’ exposure to infectious tick bites.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these changes are likely to be positive, improving survival conditions for vector and reservoir host, but others may be negative, depleting tick and/or reservoir host populations. These impacts on tick or host abundance, Borrelia infection prevalence in ticks and Borrelia population alterations may result in stable or changing risks for human to acquire the bacteria and to develop LB or RF [ 7 , 10 , 11 , 12 , 13 , 14 , 15 ]. As the human population is growing and space requirements for humans and their habitations are increasing, contact between humans, ticks and borreliae will also increase [ 15 ].…”
mentioning
confidence: 99%
“…These impacts on tick or host abundance, Borrelia infection prevalence in ticks and Borrelia population alterations may result in stable or changing risks for human to acquire the bacteria and to develop LB or RF [ 7 , 10 , 11 , 12 , 13 , 14 , 15 ]. As the human population is growing and space requirements for humans and their habitations are increasing, contact between humans, ticks and borreliae will also increase [ 15 ]. There are still many open questions that need to be addressed surrounding this complex system.…”
mentioning
confidence: 99%